How were possible main educational relations possible in distance education? - Jacek Pyżalski (Studia z Teorii Wychowania)
The text focuses on the issue of important educational relationships during crisis distance education conducted due to COVID-19 pandemic. It presents the significance of teacher-students and peer relations and their specifity during this period. Additionally, it focuses on selected research results of big scale Polish studies that explored that particular aspects of distance education and computer mediated communication. The texts concludes with analysis of crucial aspects that influence the potential of building crucial educational relations in distance education both in crisis context as well as in “normal” times.